Hypofractionated Image-Guided Radiation Therapy With Simultaneous-Integrated Boost Technique for Limited Metastases: A Multi-Institutional Analysis - Jacobs, Corbin D.; Palta, Manisha; Williamson, Hannah; Price, Jeremy G.; Czito, Brian G.; Salama, Joseph K.; Moravan, Michael J. (Frontiers in Oncology, 2019)
Purpose: To perform a multi-institutional analysis following treatment of limited osseous and/or nodal metastases in patients using a novel hypofractionated image-guided radiotherapy with simultaneous-integrated boost (HIGRT-SIB) technique. Methods: Consecutive patients treated with HIGRT-SIB for ≤5 active metastases at Duke University Medical Center or Durham Veterans’ Affairs Medical Center between 2013-2018 were analyzed to determine toxicities and recurrence patterns following treatment. Most patients received 50 Gy to the PTVboost and 30 Gy to the PTVelect simultaneously in 10 fractions. High-dose treatment volume recurrence (HDTVR) and low-dose treatment volume recurrence (LDTVR) were defined as recurrences within PTVboost and PTVelect, respectively. Marginal recurrence (MR) was defined as recurrence outside PTVelect, but within the adjacent bone or nodal chain. Distant recurrence (DR) was defined as recurrences not meeting HDTVR, LDTVR, or MR criteria. Freedom from pain recurrence (FFPR) was calculated in patients with painful osseous metastases prior to HIGRT-SIB. Outcome rates were estimated at 12 months using the Kaplan-Meier method. Results: 42 patients met inclusion criteria with 59 sites treated with HIGRT-SIB (53% nodal and 47% osseous). Median time from diagnosis to first metastasis was 31 months and the median age at HIGRT-SIB was 69 years. The most common primary tumors were prostate (36%), gastrointestinal (24%), and lung (24%). Median follow-up was 11 months. One acute grade ≥3 toxicity (febrile neutropenia) occurred after docetaxel administration immediately following HIGRT-SIB. Four patients developed late grade ≥3 toxicities: two ipsilateral vocal cord paralyses and two vertebral compression fractures. The overall pain response rate was 94% and the estimated FFPR at 12 months was 72%. The estimated 12-month rate of HDTVR, LDTVR, MR, and DR was 3.6%, 6.2%, 7.6%, and 55.8%, respectively. DR preceded MR, HDTVR, or LDTVR in each instance. Conclusion: Targeting areas at high-risk for occult disease with a lower radiation dose, while simultaneously boosting gross disease with HIGRT in patients with limited osseous and/or nodal metastases, has a high rate of treated metastasis control, a low rate of MR, acceptable toxicity, and high rate of pain palliation. Further investigation with prospective trials is warranted.